The Swelling and shrinkage properties of clay-rich soils after cement treatment: a microstructural approach - Bekhouche, Hizia; Abbeche, Khelifa; Duc, Miriam; Bahloul, Ouassila; Delage, Pierre (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"The properties of three expansive clay-rich soils from Algeria, before and after treatment with various quantities of cement was explained using physico-chemical tests. SEM, MIP and XRD as well as the adsorption of methylen blue molecule (Vbs) were carried out to observe the microstructure change under both the short term flocculating effect of Ca2+ and the long term effect of precipitated products during cement hydration (binding effect). The flocculating effect contributed also to the change of proctor optimum characteristics: γd,OPN decreased while wOPN increased with the cement addition. As expected, experimental investigations evidenced a reduction of both the swelling potentials S, the total soil deformation Stot and the swelling pressures σs when the amount of cement increased. S, Stot, σs and the shrinkage limit ws (or the liquid limit LL) versus the added cement followed a third polynomial curve, allowing to establish three swelling zones. An optimum cement content around 7-8% orresponded to the limit between zone II and III. From such limit, a maximum cohesion c’ and friction angle φ’ was reached which corresponded to a significant improvement of mechanical characteristics, while the decrease of Vbs or the maximum water content wmax stopped."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The properties of three expansive clay-rich soils from Algeria, before and after treatment with various quantities of cement was explained using physico-chemical tests. SEM, MIP and XRD as well as the adsorption of methylen blue molecule (Vbs) were carried out to observe the microstructure change under both the short term flocculating effect of Ca2+ and the long term effect of precipitated products during cement hydration (binding effect). The flocculating effect contributed also to the change of proctor optimum characteristics: γd,OPN decreased while wOPN increased with the cement addition. As expected, experimental investigations evidenced a reduction of both the swelling potentials S, the total soil deformation Stot and the swelling pressures σs when the amount of cement increased. S, Stot, σs and the shrinkage limit ws (or the liquid limit LL) versus the added cement followed a third polynomial curve, allowing to establish three swelling zones. An optimum cement content around 7-8% orresponded to the limit between zone II and III. From such limit, a maximum cohesion c’ and friction angle φ’ was reached which corresponded to a significant improvement of mechanical characteristics, while the decrease of Vbs or the maximum water content wmax stopped.